PRODUCTION OF TORREFIED BIOMASS PELLETS FROM WOODY AND AGRICULTURAL RESIDUES - Inthapat, Pimonpan; Boontanon, Suwanna Kitpati; Prachakittikul, Pensiri; Eiad-ua, Apiluck; Jadsadajerm, Supachai; Setkit, Nattawut; Worasuwannarak, Nakorn; Chaiwat, Weerawut (My University, 2023)
Two different combined process sequences of biomass pretreatment between pelletization after torrefaction (PAT) and pelletization before torrefaction (PBT) were comparatively investigated to produce torrefied biomass pellets (TBP) from woody biomasses, e.g. Leucaena (LC) and rubberwood (RW), and agricultural residues, e.g. rice straw (RS) and sugarcane leaves (SCL). In this study, each sample was thermally treated at 260-300°C for 5 min during torrefaction process. It was found that both woody biomasses and agricultural residues had mass yield lower than 63 wt%, while the bulk density of TBPs were improved higher than 400 kg/m3. For equilibrium moisture content (EMC) analysis, TBPs via PBT method had lower EMC than raw pellet after being kept at 30°C for 12 days. For the thermochemical properties, the TBPs had higher FC, %C, and HHVs than raw pellets in all biomass and increased with torrefaction temperature. When comparing the TBPs between PAT and PBT torrefied pellets, the HHVs of PBT torrefied pellets at 300°C were achieved highest at 27 MJ/kg (dry-ash-free, daf, basis) for SCL sample, which was considered as higher than the standard value at ≥21 MJ/kg of thermally treated biomass pellets (ISO/TS 17225-8:2016) and also in the range at 25.7-28.2 MJ/kg of coal. In addition, the combustion performance index (Sn) of PAT and PBT torrefied pellets was lower than raw pellets, showing a similar property as coal and lignite. Briefly, this study suggests using PBT pretreatment process to produce high quality solid fuel, particularly for agricultural residues such as SCL for a potential substitute of currently used coal.
Keywords: Biomass; fuel properties; pelletization; torrefaction; torrefied pellets